Narrative Review of Metacognition Development for Beginner Researchers (Journal of Educational Sciences, 2026)
Metacognition is the thinking about the process of cognition that helps to regulate it. The development of metacognition and metacognitive skills of learners is a broad topic, the concept and scope of which has already been outlined in the scientific literature. It is possible to develop metacognition, and the body of applied research in this area is growing. In this regard, this paper provides an overview of research on metacognition development published primarily in the journal 'Metacognition and Learning', supplemented by relevant studies from other peer-reviewed sources. Despite the abundance of articles on metacognition itself, there are not many sources of information on its development. The material presented in this article aims to be a useful aid for novice researchers into the development of metacognition in order to form initial ideas and to learn about research perspectives. Articles addressing development, facilitation, and scaffolding were manually selected from the 'Metacognition and Learning' journal, complemented by additional studies from other scholarly sources. The study differs from similar ones in that it does not concentrate on metacognition in general, but on its development. The materials were analysed using a qualitative method.  Based on the articles focusing specifically on the development of metacognition, we organized knowledge about directions for activities in the field of metacognition development. The results produced a structured knowledge that synthesises the data in the field of metacognition development. The research results also contribute to the development of theoretical ideas about the metacognition development.Keywords: metacognition, metacognitive skills, development, facilitation, theory.